The cost performance and causes of overruns in infrastructure development projects in Asia - Andrić, Jelena M.; Mahamadu, Abdul-Majeed; Wang, Jiayuan; Zou, Patrick X. W.; Zhong, Ruoyu (Journal of Civil Engineering and Management, 2019)
Infrastructure plays a major role in the economic development of countries, especially in Asia which has experienced tremendous growth in recent years. The procurement of infrastructure continues to be characterized by cost overruns resulting in significant academic interest and theoretical propositions on the influential factors. This study contributes to this issue through adoption of pragmatic research methodology involving deterministic statistical analysis of real project data from reports as well as a qualitative analysis of these reports to unearth underlying issues from a thematic analysis. Furthermore, the study design takes a multi-country view towards establishing the role of contextual and geographical influences on cost overrun. An evaluation of 102 major infrastructure projects was performed covering railways, roadways and energy sectors in different regions in Asia. Findings reveal that differences in the propensity for cost overrun are mostly dependent on a type of infrastructure with rail projects being the most likely to overrun budget. Theoretically, propositions on the influence of project contextual factors are tested highlighting the influence of project size, project type, geographical locations, and the length of implementation period of a project as well as factors related to political, economic, strategic, and competence in infrastructure delivery which vary across countries.